1989
DOI: 10.1126/science.2717945
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor in the Extracellular Matrix of Dystrophic (mdx) Mouse Muscle

Abstract: Polyclonal antibody F547 reacts with a bovine basic fibroblast growth factor (bFGF) and a human recombinant bFGF, but not with bovine acidic fibroblast growth factor. This antibody localized bFGF in the extracellular matrix of mouse skeletal muscle, primarily in the fiber endomysium, which includes the heparin-containing basal lamina. In mdx mouse muscle, which displays persistent regeneration, FGF levels in the extracellular matrix are higher than those in controls. Overabundance of matrix FGF in mdx muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
84
1

Year Published

1991
1991
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 245 publications
(89 citation statements)
references
References 31 publications
4
84
1
Order By: Relevance
“…Furthermore, it has been observed that bFGF expression is up-regulated in mdx mouse skeletal muscle and that increased levels of endogenous bFGF are present in the extracellular matrix, particularly in regenerating areas. 29,40,41 In our experiments, non-regenerating regions were also positively stained with different antibFGF antibodies in Ad-RSVbFGF-injected muscles. In addition, Ad-RSVbFGF-injected muscles showed both extracellular and specific nuclear staining whereas the contralateral muscle exhibited only scarce regions of extracellular staining.…”
Section: Discussionsupporting
confidence: 59%
“…Furthermore, it has been observed that bFGF expression is up-regulated in mdx mouse skeletal muscle and that increased levels of endogenous bFGF are present in the extracellular matrix, particularly in regenerating areas. 29,40,41 In our experiments, non-regenerating regions were also positively stained with different antibFGF antibodies in Ad-RSVbFGF-injected muscles. In addition, Ad-RSVbFGF-injected muscles showed both extracellular and specific nuclear staining whereas the contralateral muscle exhibited only scarce regions of extracellular staining.…”
Section: Discussionsupporting
confidence: 59%
“…We have not conducted an exhaustive investigation to isolate such an endogenous mitogen from the fibers, but there are several studies that detected bFGF in adult mouse muscle by immunolocalization. bFGF was detected in the myofiber periphery (potentially extracellular matrix), in nuclei within intact myofibers, and in dystrophin-positive cells in close association with the myofibers (potentially satellite cells) (DiMario et al, 1989;Anderson et al, 1991). Furthermore, transcripts for bFGF (and acidic FGF) were detected in myoblasts of mouse-and rat-derived cell lines, suggesting that endogenously produced FGFs promote proliferation of the FGFproducing myoblasts (Moore et al, 1991).…”
Section: Bfgf Promotes a Greater Number Of Satellite Cells To Enter Tmentioning
confidence: 99%
“…Sphingosine 1 phosphate induces mouse satellite cells to enter the cell cycle (Nagata et al 2006). Growth factors such as fibroblast growth factor (FGF) (DiMario and Strohman 1988;DiMario et al 1989) and insulin-like growth factor (IGF)-1 (Hill and Goldspink 2003) play a part in satellite cell proliferation and muscle regeneration (Charge and Rudnicki 2004). Other signals that are involved in controlling satellite cell function include stromal cell-derived factor (SDF)-1 that binds to CXCR4 and CXCR7 receptors on myogenic cells (Melchionna et al 2010) and M-cadherin (Irintchev et al 1994) that is involved in both satellite cell quiesence (Irintchev et al 1994) and fusion into muscle fibers (Charrasse et al 2007).…”
Section: Control Of Satellite Cell Activation and Proliferationmentioning
confidence: 99%